Regenerative Medicine May Mitigate the Need for Amputation in the Setting of a High Society for Vascular Surgery – Wound, Ischemia, Foot Infection (SVS-Wifi) Score - Poloni, Dana M; Monaco, Christina M; Ciampa, Maeghan L; Coffin, Elizabeth Marie Oliver; Liang, Joy N; Martin., Eric D (Archives of Clinical and Medical Case Reports, 2022)
Patients with diabetic foot ulcers and peripheral arterial disease are at an increased risk for developing chronic limb threatening ischemia. The Society for Vascular Surgery – Wound, Ischemia, foot Infection (WIfI) classification system assists in stratifying patients that may benefit from revascularization and those that will likely fail. With regenerative medicine, patients with high WIfI scores may have a better chance at limb salvage. This is the case of a 61-year-old male who presented with a high risk foot wound; WIfI 8 (WIfI 323). This case report highlights successful limb salvage after undergoing multiple revascularization procedures and application of regenerative medicine.